The Motion of a Rigid Body in the Presence of a Gyrostatic - Sahli, Ghadir Ahmed (Journal of natural sciences, life and applied sciences, 2019)
In this study، the rotational motion of a rigid body about a fixed point in the Newtonian force field with a gyrostatic momentum about the z-axis is considered. The equations of motion and their first integrals are obtained and reduced to a quasi-linear autonomous system with two degrees of freedom with one first integral. Poincare’s small parameter method is applied to investigate the analytical periodic solutions of the equations of motion of the body with one point fixed، rapidly spinning about one of the principal axes of the ellipsoid of inertia. A geometric interpretation of motion is given by using Euler’s angles to describe the orientation of the body at any instant of time.